Lead-acid battery separator and lead-acid battery including same

JP7643273B2Active Publication Date: 2025-03-11GS YUASA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021152475
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-17
Publication Date
2025-03-11
Estimated Expiration
2041-09-17

AI Technical Summary

Benefits of technology

【0009】 鉛蓄電池において、高いCCA性能を確保しながら、優れた重負荷寿命性能を確保することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643273000004
    Figure 0007643273000004
  • Figure 0007643273000005
    Figure 0007643273000005
  • Figure 0007643273000006
    Figure 0007643273000006
Patent Text Reader

Abstract

SOLUTION: To provide a separator for a lead battery which includes a laminate of a resin-made porous film and a glass fiber mat, wherein the porous film includes a crystalline area and an amorphous area, in an X-ray diffraction spectrum of the porous film, a ratio R represented by A1 / (A1+A2) is 0.60 or more, A1 is an area of a first diffraction peak having a highest peak height in diffraction peaks corresponding to the crystalline area, and A2 is an area of a second diffraction peak having a second higher peak height in the diffraction peaks corresponding to the crystalline area.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for a lead-acid battery and a lead-acid battery including the same. [Background technology]

[0002] Lead-acid batteries are used in various applications, including automotive and industrial applications. A lead-acid battery includes a positive electrode plate, a negative electrode plate, a separator interposed between the positive electrode plate and the negative electrode plate, and an electrolyte. Various performance characteristics are required of the separator of a lead-acid battery. A porous film made of polyolefin is generally used as the separator.

[0003] Patent Document 1 proposes a separator for a lead acid battery comprising a polyolefin microporous membrane, the polyolefin microporous membrane comprising polyethylene, preferably ultra-high molecular weight polyethylene, a particulate filler, and a treatment plasticizer, the particulate filler being present in an amount of 40% or more by weight, the polyethylene comprising a shish-kebab-formed polymer comprising a plurality of extended chain crystals (shish formation) and a plurality of folded chain crystals (kebab formation), the average repetition or period of the kebab formation being from 1 nm to 150 nm, preferably less than 120 nm.

[0004] In some cases, a porous film and a glass mat are used together as a separator. For example, Patent Document 2 proposes a lead-acid battery including a positive electrode plate, a negative electrode plate, an electrolyte, and a separator, the separator being made of a porous sheet and a glass mat, and the electrolyte containing 0.02 mol / L or more and 0.2 mol / L or less of aluminum ions and 0.02 mol / L or more and 0.2 mol / L or less of lithium ions.

[0005] Patent Document 3 proposes a lead-acid battery in which a separator made of a porous resin thin film and a glass mat is interposed between positive and negative plates, and a group of electrodes formed by alternately stacking these is housed in a battery case, characterized in that (a) at least one side of the base part of the synthetic resin thin film is provided with a plurality of rib parts, (b) a glass mat is attached between each of the rib parts, and (c) a glass mat is also attached to the outside of the rib parts at both ends, and further, (d) when the glass mat is attached to the base part of the synthetic resin thin film, the surface of the glass mat on the opposite side to the attached surface has a thickness that is higher than the top surface of the rib part, and (e) when the separator with the glass mat attached to the synthetic resin thin film is inserted into the group of electrodes and housed in the battery case of the lead-acid battery, the glass mat is compressed under pressure until the rib part abuts against the positive plate, and the stacking pressure is 10 to 60 kPa. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2019-514173 [Patent Document 2] JP 2013-84362 A [Patent Document 3] JP 2016-139455 A Summary of the Invention [Problem to be solved by the invention]

[0007] In lead-acid batteries, the positive electrode material softens when the battery is repeatedly charged and discharged. As in Patent Documents 2 and 3, the provision of a glass fiber mat is advantageous in reducing the shedding of the softened positive electrode material. However, in a separator that is a laminate, the resistance is higher than that in the case of only a porous film, and the cold cranking ampere (CCA) performance is reduced. The reduction in the CCA performance can be reduced by reducing the thickness of the porous film. However, since the thickness of the glass fiber mat is not so large, the fallen positive electrode material or the end of the current collector is likely to penetrate the glass fiber mat. If the thickness of the porous film constituting the laminate is small, the porous film breaks and shorts out, and the life performance in the heavy load life test is reduced. Therefore, it is difficult to ensure excellent life performance in the heavy load life test while ensuring high CCA performance. Hereinafter, the life performance in a heavy load cycle such as a heavy load life test may be simply referred to as the heavy load life performance. [Means for solving the problem]

[0008] One aspect of the present disclosure is a separator for a lead-acid battery, the separator includes a laminate of a porous resin film and a glass fiber mat, The porous film includes a crystalline region and an amorphous region, In the X-ray diffraction spectrum of the porous film, the ratio R represented by A1 / (A1+A2) is 0.60 or more; A1 is the area of ​​the first diffraction peak having the maximum peak height among the diffraction peaks corresponding to the crystalline region, A2 relates to a separator for a lead-acid battery, which is the area of ​​a second diffraction peak having the second highest peak height among the diffraction peaks corresponding to the crystalline region. Effect of the Invention

[0009] In lead-acid batteries, it is possible to ensure excellent heavy load life performance while ensuring high CCA performance. [Brief description of the drawings]

[0010] [Figure 1] 1 is a partially cutaway perspective view showing the appearance and internal structure of a lead-acid battery according to one embodiment of the present invention; [Diagram 2] FIG. 2 is a schematic plan view of the separator of FIG. [Diagram 3] 1 is an X-ray diffraction spectrum of a porous film used in a separator of the lead-acid battery E7 of an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] A lead-acid battery separator according to one aspect of the present invention includes a laminate of a resin porous film and a glass fiber mat. The porous film includes a crystalline region and an amorphous region. In an X-ray diffraction (XRD) spectrum of the porous film, a ratio R expressed as A1 / (A1+A2) is 0.60 or more. Here, A1 is the area of ​​a diffraction peak (first diffraction peak) having the maximum peak height among the diffraction peaks corresponding to the crystalline region. A2 is the area of ​​a diffraction peak (second diffraction peak) having the second highest peak height among the diffraction peaks corresponding to the crystalline region.

[0012] The ratio R indicates the degree of crystallinity of the porous film. In the porous film used in the conventional separator, the ratio R tends to be relatively low, for example, about 0.58 or less. In contrast, in the separator of the above aspect, the ratio R of the porous film is 0.60 or more, and a porous film with higher crystallinity than the conventional one is used. By increasing the crystallinity of the porous film constituting the separator, the strength of the porous film itself (specifically, piercing strength) can be improved. Therefore, even if the end of the fallen positive electrode material or the current collector penetrates the glass fiber mat and contacts the porous film, it is possible to suppress the short circuit caused by the penetration of the porous film or the breakage of the porous film due to oxidative deterioration. This can improve the life performance in the heavy load life test, which is a condition under which the positive electrode material is likely to fall off. By setting the ratio R of the porous film to 0.60 or more, a certain degree of strength can be secured even if the thickness of the porous film is reduced. Since high heavy load life performance can be obtained even if the thickness of the porous film is reduced, the deterioration of CCA performance can be suppressed. In this way, it is possible to ensure excellent heavy load life performance while ensuring high CCA performance.

[0013] In this specification, the heavy load life performance refers to the life performance when a cycle of discharge and charge is repeated in a region where the depth of discharge in one cycle is 20% or more (also called the heavy load region) when the rated capacity (5-hour rate capacity) is taken as 100%. Such a cycle of discharge and charge is sometimes called a heavy load cycle.

[0014] In addition, the porous film itself may be used as a separator for a lead-acid battery. Unlike separators for lithium-ion secondary batteries, etc., a porous film separator for a lead-acid battery has a certain degree of thickness. In addition, the thicker the porous film, the more difficult it tends to be to increase the crystallinity, and as the crystallinity increases, the porous film tends to become hard and brittle. From this perspective, the crystallinity has not been controlled in the conventional porous films used in separators for lead-acid batteries. In contrast to such conventional common sense, in the lead-acid battery separator according to one aspect of the present invention, by setting the ratio R of the porous film laminated to the glass fiber mat to 0.60 or more, it is possible to ensure high strength while keeping the resistance of the porous film low, and to suppress an increase in the resistance of the laminate with the glass fiber mat.

[0015] The thickness of the porous film is preferably 100 μm or more. When the thickness is in this range, it is easy to ensure higher strength and higher heavy load life performance. The thickness of the porous film is preferably 300 μm or less. In this case, it is easy to keep the resistance of the porous film low, so that a relatively high CCA performance is easily obtained.

[0016] The ratio R is preferably 0.9 or less. In this case, the flexibility of the porous film is easily ensured while suppressing deterioration of the porous film, and the production is easy.

[0017] The porous film preferably contains a polyolefin, more preferably contains a polyolefin containing at least an ethylene unit. Although such a porous film tends to have a relatively low strength, the ratio R is relatively easy to adjust, and the strength of the separator can be increased by adjusting the ratio R. When the porous film contains a polyolefin containing at least an ethylene unit, the first diffraction peak corresponds to the (110) plane due to the crystalline region, and the second diffraction peak corresponds to the (200) plane due to the crystalline region.

[0018] The porous film may have an area not covered with the glass fiber mat at least in a part of the end. In such an area, the fallen positive electrode material may pierce the porous film or come into contact with the porous film and cause oxidative deterioration, which may cause a short circuit and reduce the life performance in the heavy load life test. However, even in such a case, the high ratio R of the porous film can improve the strength of the porous film itself, thereby reducing the occurrence of a short circuit.

[0019] The present invention also includes a lead-acid battery including the above-mentioned separator for lead-acid batteries. The lead-acid battery includes at least one cell including an electrode plate group and an electrolyte, and the electrode plate group includes a positive electrode plate, a negative electrode plate, and the above-mentioned separator interposed between the positive electrode plate and the negative electrode plate. Here, the glass fiber mat of the separator is in contact with the positive electrode plate. By using the above-mentioned separator, the resistance of the separator can be kept low, and high CCA performance can be ensured. By obtaining high strength of the porous film, the breakage of the porous film due to the fallen positive electrode material or the end of the current collector is suppressed, and the occurrence of a short circuit is suppressed, so that excellent heavy load life performance can be ensured.

[0020] The lead-acid battery may be a valve regulated battery, but is preferably a flooded battery (vented battery), which is sometimes called a Valve Regulated Lead-Acid Battery (VRLA).

[0021] In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, battery case, separator, etc.) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal, and in a flooded battery, the lug is provided on the top of the plate so as to protrude upward.

[0022] Hereinafter, a separator and a lead-acid battery according to an embodiment of the present invention will be described in more detail with reference to the drawings. However, the present invention is not limited to the following embodiment.

[0023] (Separator) The separator includes a laminate of a porous resin film and a glass fiber mat.

[0024] (Porous film) A porous film includes a crystalline region in which the molecules of the constituent material (specifically, a resin material) of the porous film are arranged relatively regularly (i.e., highly ordered), and an amorphous region in which the molecules are less ordered. Therefore, in the XRD spectrum of the porous film, diffraction peaks due to the crystalline region are observed, and scattered light due to the amorphous region is observed as a halo. In the XRD spectrum of the porous film, when the ratio R represented by A1 / (A1+A2) is 0.60 or more, the porous film has high strength. Here, A1 is the area of ​​the diffraction peak (first diffraction peak) having the maximum peak height among the diffraction peaks corresponding to the crystalline region, and A2 is the area of ​​the diffraction peak (second diffraction peak) having the second highest peak height among the diffraction peaks corresponding to the crystalline region.

[0025] For example, in the XRD spectrum of a porous film containing a polyolefin containing ethylene units, a diffraction peak corresponding to the (110) plane of the crystalline region is observed in the range of 2θ from 20° to 22.5°, and a diffraction peak corresponding to the (200) plane of the crystalline region is observed in the range of 2θ from 23° to 24.5°. A halo of the amorphous region is observed in the range of 2θ from 17° to 27°. Among the diffraction peaks due to the crystalline region, the diffraction peak corresponding to the (110) plane has the maximum peak height and corresponds to the first diffraction peak. The diffraction peak corresponding to the (200) plane has the second highest peak height and corresponds to the second diffraction peak.

[0026] The ratio R is 0.60 or more, and from the viewpoint of ensuring a higher strength of the porous film, it may be 0.65 or more, 0.70 or more, or 0.75 or more. The ratio R may be 0.9 or less, 0.85 or less, or 0.80 or less. When the ratio R is in such a range, it is easy to ensure the flexibility of the separator, and the production is easy.

[0027] The ratio R is 0.60 or more (or 0.65 or more) and 0.9 or less, 0.60 or more (or 0.65 or more) and 0.85 or less, 0.60 or more (or 0.65 or more) and 0.80 or less, It may be 0.70 or more (or 0.75 or more) and 0.9 or less, 0.70 or more (or 0.75 or more) and 0.85 or less, or 0.70 or more (or 0.75 or more) and 0.80 or less.

[0028] The areas of the diffraction peaks are determined by fitting the diffraction peaks due to the crystalline regions in the XRD spectrum of the porous film. The ratio R is calculated from the above formula using the area A1 of the first diffraction peak and the area A2 of the second diffraction peak.

[0029] The porous film, for example, includes a polymer material (hereinafter also referred to as a base polymer). Since the porous film includes a crystalline region, the base polymer usually includes a crystalline polymer. The porous film, for example, includes a polyolefin. A polyolefin is a polymer that includes at least an olefin unit (i.e., a polymer that includes at least a monomer unit derived from an olefin).

[0030] As the base polymer, polyolefin may be used in combination with other base polymers. The ratio of polyolefin to the entire base polymer contained in the porous film is, for example, 50% by mass or more, may be 80% by mass or more, or may be 90% by mass or more. The ratio of polyolefin is, for example, 100% by mass or less. The base polymer may be composed of only polyolefin. When the ratio of polyolefin is so high, the strength of the porous film tends to be low, but even in such a case, the ratio R is set to the above range, so that high strength can be ensured.

[0031] Polyolefins include, for example, homopolymers of olefins, copolymers containing different olefin units, and copolymers containing olefin units and copolymerizable monomer units. The copolymers containing olefin units and copolymerizable monomer units may contain one or more types of olefin units. The copolymers containing olefin units and copolymerizable monomer units may contain one or more types of copolymerizable monomer units. The copolymerizable monomer units are monomer units derived from polymerizable monomers other than olefins and copolymerizable with olefins.

[0032] The polyolefin may, for example, be at least C 2-3 Polymers containing olefins as monomer units are also included. 2-3 The olefin may be at least one selected from the group consisting of ethylene and propylene. The polyolefin may be, for example, polyethylene, polypropylene, C 2-3 Copolymers containing olefin as a monomer unit (e.g., ethylene-propylene copolymer) are more preferred. Among polyolefins, polyolefins containing at least ethylene units (polyethylene, ethylene-propylene copolymer, etc.) are preferably used. Polyolefins containing ethylene units (polyethylene, ethylene-propylene copolymer, etc.) may be used in combination with other polyolefins.

[0033] The porous film preferably contains oil. When the porous film contains oil, the effect of suppressing oxidation degradation of the porous film is enhanced. Even if the fallen positive electrode material comes into contact with the porous film, the oxidation degradation of the porous film is suppressed, so that the occurrence of breakage can be further reduced.

[0034] The oil refers to a hydrophobic substance that is liquid at room temperature (a temperature between 20°C and 35°C) and separates from water. The oil includes naturally derived oils, mineral oils, and synthetic oils. The oil is preferably a mineral oil or a synthetic oil. The oil may be, for example, paraffin oil or silicone oil. The porous film may contain one type of oil or a combination of two or more types of oil.

[0035] The oil content in the porous film is preferably 11% by mass or more and 18% by mass or less. When the oil content is in this range, the effect of suppressing oxidation deterioration of the porous film is further enhanced. In addition, the resistance of the separator can be kept relatively low.

[0036] The porous film may be in a sheet shape. Also, the sheet-shaped porous film may be folded in an accordion shape and used as a separator. The porous film may be formed in a bag shape. Either the positive electrode plate or the negative electrode plate may be housed in the bag-shaped porous film.

[0037] The porous film may or may not have ribs. The porous film having ribs includes, for example, a base portion and ribs standing on the surface of the base portion. The ribs may be provided on only one surface of the porous film or each of the base portions, or may be provided on both surfaces. The base portion of the porous film refers to the portion of the porous film that excludes protrusions such as ribs, and is a sheet-like portion that defines the outer shape of the porous film.

[0038] The thickness of the porous film is, for example, 90 μm or more. From the viewpoint of obtaining higher strength, 100 μm or more is preferable. The thickness of the porous film is, for example, 300 μm or less, and may be 250 μm or less. From the viewpoint of keeping the resistance of the porous film low and easily ensuring higher CCA performance, the thickness of the porous film is preferably 200 μm or less, and may be 150 μm or less. Even if the thickness of the porous film is so small, sufficient strength can be obtained and high heavy load life performance can be ensured. The thickness of the porous film means the average thickness of the part of the porous film facing the electrode material. When the porous film has a base portion and a rib erected from at least one surface of the base portion, the thickness of the porous film is the average thickness of the base portion.

[0039] The thickness of the porous film may be 90 μm or more (or 100 μm or more) and 300 μm or less, 90 μm or more (or 100 μm or more) and 250 μm or less, 90 μm or more (or 100 μm or more) and 200 μm or less, or 90 μm or more (or 100 μm or more) and 150 μm or less.

[0040] When the porous film has ribs, the height of the ribs may be 50 μm or more. Also, the height of the ribs may be 1.2 mm or less. The height of the ribs is the height of the part protruding from the surface of the base part (protruding height).

[0041] In the above aspect of the present invention, the ribs of the porous film may be provided on the surface on the negative electrode plate side. In this case, the ribs are preferably provided on the portion of the porous film facing the negative electrode material. By providing the ribs on the negative electrode plate side, the electrolyte can be easily diffused. The height of the ribs provided on the negative electrode plate side is, for example, 50 μm or more. The height of the ribs may be, for example, 400 μm or less or 300 μm or less.

[0042] When ribs are provided on the positive electrode plate side of the porous film, they may be provided in an area not covered with the glass fiber mat. When ribs are provided in a portion facing the positive electrode material, the glass fiber mat may be disposed between adjacent ribs as in Patent Document 2. However, in consideration of the ease of lamination with the glass fiber mat, it is not necessary to provide ribs on the positive electrode plate side of the porous film.

[0043] The porous film may have an area not covered by the glass fiber mat at at least a part of the end. If the fallen positive electrode material comes into contact with this area, the porous film may be oxidized and deteriorated, or the positive electrode material may be embedded in the porous film, causing the porous film to break and a short circuit, which may shorten the life of the porous film. However, in the above aspect of the present invention, even in such a case, the strength of the porous film is increased, thereby suppressing the breakage of the porous film and the occurrence of a short circuit. The porous film is roughly rectangular, and usually has a total of four ends, including the top and bottom ends and both side ends. The width of the area of ​​the porous film not covered by the glass fiber mat at one end (for example, w in FIG. 2 described later) is p ) is, for example, 1 mm or more, and may be 2 mm or more. The width of this region may be, for example, 5 mm or less, 4.5 mm or less, or 4 mm or less. The porous film may have a region at the side end (preferably both side ends) that is not covered with the glass fiber mat. When a bag-shaped porous film and a glass fiber mat are laminated, a predetermined region at the side end including the portion compressed into a bag shape is exposed outside the glass fiber mat.

[0044] The width of the above-mentioned region may be 1 mm or more (or 2 mm or more) and 5 mm or less, 1 mm or more (or 2 mm or more) and 4.5 mm or less, or 1 mm or more (or 2 mm or more) and 4 mm or less.

[0045] The porous film can be obtained, for example, by extruding a resin composition containing a base polymer, a pore-forming agent, and a penetrating agent (surfactant) into a sheet, stretching the resin composition, and then removing at least a portion of the pore-forming agent. By removing at least a portion of the pore-forming agent, micropores are formed in the matrix of the base polymer. After removing the pore-forming agent, the sheet-shaped porous film is dried as necessary. For example, the ratio R is adjusted by adjusting at least one selected from the group consisting of the cooling rate of the sheet during extrusion molding, the stretching ratio during stretching, and the temperature during drying. For example, the ratio R tends to be higher when the sheet is quenched during extrusion molding, the stretching ratio is increased, or the temperature during drying is decreased. The stretching process may be performed by biaxial stretching, but is usually performed by uniaxial stretching. The sheet-shaped porous film may be folded into a bellows shape or processed into a bag shape as necessary.

[0046] In a porous film having ribs, the ribs may be formed on the sheet when the resin composition is extruded, or may be formed by pressing the sheet with a roller having grooves corresponding to each rib after the resin composition is molded into a sheet or after the pore-forming agent is removed.

[0047] Examples of the pore-forming agent include liquid pore-forming agents and solid pore-forming agents. The pore-forming agent preferably contains at least oil. By using oil, a porous film containing oil can be obtained, and the effect of suppressing oxidative deterioration can be enhanced. The pore-forming agent may be used alone or in combination of two or more. Oil may be used in combination with another pore-forming agent. A liquid pore-forming agent may be used in combination with a solid pore-forming agent. At room temperature (a temperature of 20°C or higher and 35°C or lower), a liquid pore-forming agent is classified as a liquid pore-forming agent, and a solid pore-forming agent is classified as a solid pore-forming agent.

[0048] The liquid pore-forming agent is preferably the above-mentioned oil, and the solid pore-forming agent is, for example, a polymer powder.

[0049] The amount of the pore-forming agent in the porous film may vary depending on the type. The amount of the pore-forming agent in the porous film is, for example, 30 parts by mass or more per 100 parts by mass of the base polymer. The amount of the pore-forming agent is, for example, 60 parts by mass or less per 100 parts by mass of the base polymer.

[0050] For example, a porous film containing oil is formed by extracting and removing a part of the oil from a sheet formed using oil as a pore-forming agent using a solvent. The solvent is selected, for example, according to the type of oil. For example, the content of oil in the porous film is adjusted by adjusting the type and composition of the solvent, extraction conditions (extraction time, extraction temperature, solvent supply speed, etc.), etc.

[0051] The surfactant as the penetrating agent may be, for example, either an ionic surfactant or a nonionic surfactant. The surfactant may be used alone or in combination of two or more kinds.

[0052] The content of the penetrant in the porous film is, for example, 0.01% by mass or more, and may be 0.1% by mass or more. The content of the penetrant in the porous film may be 10% by mass or less.

[0053] The porous film (or the resin composition used to produce the porous film) may contain inorganic particles.

[0054] The inorganic particles are preferably, for example, ceramic particles. Examples of ceramics constituting the ceramic particles include at least one selected from the group consisting of silica, alumina, and titania.

[0055] The content of inorganic particles in the porous film may be, for example, 40% by mass or more.The content of inorganic particles may be, for example, 80% by mass or less, or 70% by mass or less.

[0056] (fiberglass mat) The glass fiber mat is laminated on the surface of the porous film facing the positive electrode plate. For example, in the case of a bag-shaped porous film, the glass fiber mat may be laminated on both outer surfaces of the bag. For example, when the electrode plate at the end of the electrode plate group is a negative electrode plate, the bag-shaped porous film that houses the negative electrode plate may have the glass fiber mat laminated on the surface facing the positive electrode plate, and the surface not facing the positive electrode plate may have the porous film exposed.

[0057] The fiberglass mat is a mat (or nonwoven fabric) made of glass fibers. The fiberglass mat may be a material called Absorbent Glass Mat (AGM).

[0058] The glass fiber mat may be entirely made of glass fibers. The glass fiber mat may contain glass fibers as a main component. The glass fiber mat may have a glass fiber content of 90% by mass or more, or 95% by mass or more. The glass fiber mat has a glass fiber content of 100% by mass or less. The glass fiber mat may contain components other than glass fibers, such as organic fibers, acid-resistant inorganic powder, and polymers as binders, but the content of these components is usually 10% by mass or less, or 5% by mass or less.

[0059] The average fiber diameter of the glass fibers is, for example, 0.1 μm or more, and may be 0.5 μm or more. When the average fiber diameter of the glass fibers is in such a range, the effect of suppressing the falling off of the softened positive electrode material is enhanced. The average fiber diameter of the glass fibers is, for example, 30 μm or less, and may be 10 μm or less. In this case, the internal resistance of the battery can be suppressed from increasing excessively. In addition, the glass fiber mat can be secured to have a relatively high flexibility, and can easily hold a relatively large amount of electrolyte.

[0060] The average fiber diameter of the glass fibers may be 0.1 μm or more (or 0.5 μm or more) and 30 μm or less, or 0.1 μm or more (or 0.5 μm or more) and 10 μm or less.

[0061] The surface density of the glass fiber mat is, for example, 100 g / m 2 That's all. The surface density of the glass fiber mat is 250g / m 2 It may be less than 200 g / m 2 It may be the following.

[0062] The separator can be obtained, for example, by laminating a porous film and a glass fiber mat. More specifically, the separator can be formed by laminating a glass fiber mat on the surface of the porous film facing the positive electrode plate. The porous film and the glass fiber mat can be simply stacked, or can be laminated (or fixed) using an adhesive. The porous film and the glass fiber mat can also be laminated (or fixed) using welding (heat sealing, etc.) or mechanical bonding methods (gear sealing, etc.). Examples of the adhesive include silicone adhesives, epoxy adhesives, and polyolefin adhesives. It is preferable to apply a small amount of adhesive so that the resistance of the separator does not increase. For example, it is preferable to apply the adhesive partially rather than to the entire surface of the porous film or glass fiber mat to be bonded.

[0063] (Analysis or size measurement of porous films and fiberglass mats) (Preparation of separator) For the analysis or size measurement of the porous film or glass fiber mat, a separator that has not been used or that has been removed from a lead-acid battery in a fully charged state is used. The separator removed from the lead-acid battery is washed and dried prior to the analysis or measurement.

[0064] The separator removed from the lead-acid battery is washed and dried according to the following procedure. The separator is immersed in pure water for one hour to remove the sulfuric acid from the separator. The separator is then removed from the liquid and left to stand for at least 16 hours in an environment of 25°C ± 5°C to dry.

[0065] In this specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D 5301:2019. More specifically, the fully charged state is a state in which a lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) that is 1 / 10 of the value described as the rated capacity, until the terminal voltage (V) during charging measured every 15 minutes or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is a state in which constant current and constant voltage charging of 2.23V / cell is performed in an air tank at 25°C ± 2°C with a current (A) that is 0.2 times the value (unit: Ah) described as the rated capacity, and charging is terminated when the charging current during constant voltage charging becomes 0.005 times the value (unit: Ah) described as the rated capacity. The value described as the rated capacity is a value in Ah. The unit of current set based on the value stated as the rated capacity is A.

[0066] A fully charged lead-acid battery is a lead-acid battery that has already been chemically formed and is fully charged. The lead-acid battery may be fully charged immediately after chemical formation, or after a certain period of time has passed since chemical formation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical formation may be fully charged).

[0067] In this specification, a battery in its early stages of use refers to a battery that has not been in use for a long time and has hardly deteriorated at all.

[0068] (XRD spectrum) The XRD spectrum of the porous film is measured by irradiating the surface of the porous film facing the positive electrode plate with X-rays perpendicularly. A sample for measurement is prepared by peeling the glass fiber mat from the porous film of the separator and processing the area not coated with adhesive into a strip. For porous films with ribs on the surface facing the positive electrode plate, the sample is processed so that it does not include the ribs. The measurement and fitting of the XRD spectrum are performed under the following conditions. (Measurement conditions) Measurement device: RINT-TTR2, manufactured by Rigaku Corporation Fitting: FT (step scan) method Measurement angle range: 15-35° Step width: 0.02° Measurement speed: 5° / min XRD data processing: XRD pattern analysis software (PDXL2, Rigaku) ​​was used.

[0069] (Porous film thickness and rib height) The thickness of the porous film is determined by measuring the thickness of the porous film portion at five arbitrarily selected points in a cross-sectional photograph of the separator and averaging the measured values.

[0070] The height of the rib is determined by averaging the heights of the base portion of the rib from one surface, measured at 10 arbitrarily selected points on the rib in a cross-sectional photograph of the separator.

[0071] (Oil content in porous film) In the separator, the glass fiber mat is peeled off from the porous film. The area where the adhesive is not applied, which faces the electrode material of the separator, is processed into a rectangular shape to prepare a sample (hereinafter referred to as Sample A). In the case where the porous film has ribs, Sample A is processed so that it does not include the ribs.

[0072] Approximately 0.5 g of sample A is taken and accurately weighed to determine the initial mass of the sample (m0). The weighed sample A is placed in a glass beaker of appropriate size, and 50 mL of n-hexane is added. Next, ultrasonic waves are applied to the sample together with the beaker for approximately 30 minutes to dissolve the oil contained in sample A into n-hexane. Next, the sample is removed from n-hexane, dried in air at room temperature (temperature between 20°C and 35°C), and then weighed to determine the mass (m1) of the sample after removing the oil. Then, the oil content is calculated using the following formula. The oil content of 10 samples A is calculated and the average value is calculated. The obtained average value is taken as the oil content in the porous film. Oil content (mass%) = (m0-m1) / m0 x 100

[0073] (Content of inorganic particles in porous film) A portion of sample A prepared in the same manner as above is taken, accurately weighed, and then placed in a platinum crucible and heated with a Bunsen burner until no white smoke is emitted. The obtained sample is then heated in an electric furnace (in oxygen flow, 550°C ± 10°C) for approximately 1 hour to be incinerated, and the incinerated material is weighed. The ratio (percentage) of the mass of the incinerated material to the mass of sample A is calculated, and this is regarded as the inorganic particle content (mass%) described above. The inorganic particle content is determined for 10 samples A, and the average value is calculated. The obtained average value is regarded as the inorganic particle content in the porous film.

[0074] (Content of penetrant in porous film) A portion of sample A prepared in the same manner as above is taken, weighed accurately, and then dried for 12 hours or more at room temperature (temperature between 20°C and 35°C) in a reduced pressure environment lower than atmospheric pressure. The dried material is placed in a platinum cell and set in a thermogravimetric measuring device, and the temperature is raised from room temperature to 800°C ± 1°C at a heating rate of 10K / min. The weight loss amount when the temperature is raised from room temperature to 250°C ± 1°C is taken as the mass of the penetrant, and the ratio (percentage) of the mass of the penetrant to the mass of sample B is calculated, and this is taken as the content (mass%) of the penetrant. A Q5000IR manufactured by TA Instruments is used as the thermogravimetric measuring device. The content of the penetrant is determined for 10 pieces of sample A, and the average value is calculated. The obtained average value is taken as the content of the penetrant in the porous film.

[0075] (Average fiber diameter of glass fiber mat) The average fiber diameter of the glass fibers is determined by determining the maximum diameter of any 100 fibers taken from the glass fiber mat portion of the separator in any cross section perpendicular to the length direction, and averaging the maximum diameter.

[0076] (Glass mat surface density) The portion of the separator facing the electrode material is cut, and the portion not coated with adhesive is sampled and weighed, and the vertical and horizontal dimensions of the glass fiber mat portion (in other words, the vertical and horizontal dimensions of the cut portion) are measured. The glass fiber mat is peeled off from the cut portion and the mass of the porous film is measured. The mass of the glass fiber mat portion is calculated by subtracting the mass of the porous film from the mass of the cut portion. The area is calculated from the vertical and horizontal dimensions of the glass fiber mat portion and is expressed as 1 m 2 The mass (g) of the glass fiber mat per unit is calculated as the areal density.

[0077] (Positive plate) A paste-type positive electrode plate is used as the positive electrode plate. The paste-type positive electrode plate includes a positive electrode collector and a positive electrode material. The positive electrode material is held by the positive electrode collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode collector. Note that a member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is used integrally with the electrode plate, and is therefore included in the electrode plate. When the positive electrode plate includes an attachment member, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode collector and the attachment member.

[0078] The positive electrode current collector included in the positive electrode plate may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead or lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0079] As the lead alloy used for the positive electrode current collector, a Pb-Ca alloy or a Pb-Ca-Sn alloy is preferable in terms of corrosion resistance and mechanical strength. The positive electrode current collector may have lead alloy layers with different compositions, and the alloy layer may be one layer or multiple layers.

[0080] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives (such as a reinforcing material) as necessary.

[0081] Examples of reinforcing materials include fibers (inorganic fibers, organic fibers, etc.). Examples of resins (or polymers) constituting the organic fibers include at least one selected from the group consisting of acrylic resins, polyolefin resins (polypropylene resins, polyethylene resins, etc.), polyester resins (including polyalkylene arylates (polyethylene terephthalate, etc.)), and celluloses (cellulose, cellulose derivatives (cellulose ether, cellulose ester, etc.)). Celluloses also include rayon.

[0082] The content of the reinforcing material in the positive electrode material is, for example, 0.03 mass % or more, and, for example, the content of the reinforcing material in the positive electrode material is, for example, 0.5 mass % or less.

[0083] Unformed paste-type positive plate is obtained by filling a positive current collector with a positive paste, aging and drying it. The positive paste is prepared by adding water and sulfuric acid to lead powder, an antimony compound, and other additives (such as reinforcing materials) as necessary, and kneading them.

[0084] A positive plate is obtained by chemically forming an unformed positive plate. Chemical formation can be performed by immersing an electrode plate group including an unformed positive plate in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group. However, chemical formation may be performed before assembling the lead-acid battery or the electrode plate group.

[0085] (Negative plate) The negative electrode plate of a lead-acid battery is composed of a negative current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative current collector. Note that an attachment member as described above may be attached to the negative electrode plate. In this case, the attachment member is included in the negative electrode plate. In the case where the negative electrode plate includes an attachment member, the negative electrode material is the portion of the negative electrode plate excluding the negative current collector and the attachment member.

[0086] The negative electrode current collector can be formed in the same manner as the positive electrode current collector.

[0087] The lead alloy used in the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have lead alloy layers with different compositions, and the alloy layer may be one layer or multiple layers.

[0088] The negative electrode material contained in the negative plate contains a negative electrode active material (lead or lead sulfate) that develops capacity through an oxidation-reduction reaction, and may contain an organic shrinkage inhibitor, a carbonaceous material, barium sulfate, etc. The negative electrode material may contain other additives (such as a reinforcing material) as necessary.

[0089] Examples of the organic shrinkage inhibitor include lignin, lignin sulfonic acid, synthetic organic shrinkage inhibitors (such as formaldehyde condensates of phenol compounds), etc. The negative electrode material may contain one type of organic shrinkage inhibitor, or may contain two or more types.

[0090] The content of the organic shrink-preventing agent in the negative electrode material is, for example, 0.01% by mass or more, and, for example, 1% by mass or less.

[0091] Examples of the carbonaceous material include carbon black, graphite (artificial graphite, natural graphite, etc.), hard carbon, soft carbon, etc. The negative electrode material may contain one type of carbonaceous material or may contain two or more types of carbonaceous materials.

[0092] The content of the carbonaceous material in the negative electrode material is, for example, 0.1% by mass or more. The content of the carbonaceous material may be, for example, 3% by mass or less.

[0093] The content of barium sulfate in the negative electrode material is, for example, 0.1% by mass or more, and, for example, 3% by mass or less.

[0094] Examples of the reinforcing material include fibers (inorganic fibers, organic fibers (such as organic fibers made of resin described as the reinforcing material for the positive electrode material)).

[0095] The content of the reinforcing material in the negative electrode material is, for example, 0.03 mass % or more, and, for example, the content of the reinforcing material in the negative electrode material is, for example, 0.5 mass % or less.

[0096] The negative active material in the charged state is sponge lead, but the unformed negative plate is usually made from lead powder.

[0097] The negative electrode plate can be formed by filling a negative electrode current collector with a negative electrode paste, aging and drying the negative electrode paste to produce an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is produced by adding water and sulfuric acid to lead powder, an organic shrinkage inhibitor, and various additives as necessary, and kneading them. In the aging process, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.

[0098] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0099] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled as necessary.

[0100] The electrolyte may further contain at least one metal ion selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.

[0101] The specific gravity of the electrolyte at 20° C. is, for example, 1.10 or more. The specific gravity of the electrolyte at 20° C. may be 1.35 or less. Note that these specific gravities are values ​​for the electrolyte of a lead-acid battery in a fully charged state.

[0102] The evaluation method for each characteristic will be described below.

[0103] (1) Puncture strength The puncture strength of the separator (porous film) is measured by the following procedure. In accordance with JIS Z 1707:2019, 7.5 "Puncture Strength Test", a test piece including the edge of the separator (more specifically, the edge of both side ends of the porous film exposed from the glass fiber mat of the separator) is fixed in a jig, the needle of the test machine is pierced into the edge, and the maximum force (N) until the needle penetrates is measured. Five test pieces are measured in the same manner, and the average value is calculated and used as the piercing strength. The test piece is prepared by cutting the separator (the above-mentioned edge of the porous film) to a size of 50 mm long x 50 mm wide so as to include the edge. In the case where a crimped portion is formed on both side ends of the porous film in a bag-shaped porous film, the piercing strength is measured for the part other than the crimped portion of the edge. The test machine used is AGS-X, 10N-10kN manufactured by Shimadzu Corporation. The needle used is a needle with a diameter of 1.0 mm and a semicircular tip shape (radius 0.5 mm), and the test speed is 50±5 mm / min. The jig used to fix the test piece has a diameter of 10 mm on the top surface of the measurement section and a diameter of 20 mm on the bottom surface.

[0104] (2)CCA performance In accordance with JIS D 5301:2019, the starting ability of a lead-acid battery is evaluated using the current value at which the terminal voltage is 7.2 V or higher 30 seconds after the start of discharge, using the following procedure. A higher current value indicates higher starting ability and lower separator resistance. (a) After fully charging, place the battery in a cooling room at -18°C ± 1°C for at least 16 hours. (b) After confirming that the electrolyte temperature of one of the central cells is -18℃±1℃, discharge it for 30 seconds using CCA390A. (c) Record the terminal voltage 30 seconds after the discharge begins.

[0105] (3) Heavy load life performance The heavy load life performance is evaluated as follows. A heavy load test is performed in accordance with JIS D 5301:2019 9.5.5 Life Test b) Heavy load life test. More specifically, a fully charged lead-acid battery is first discharged for 1 hour at the discharge current shown in Table 1, and then charged for 5 hours at the charge current shown in Table 1. This cycle of discharge and charge is considered as one cycle. The discharge current and discharge current are changed as shown in Table 1 according to the 5-hour rate capacity of the lead-acid battery. The following explanation of the heavy load test is an example of using a lead-acid battery with a 5-hour rate capacity of 48 Ah. During the test, the lead-acid battery is placed in a water tank at 40°C ± 2°C. The water surface of the tank is positioned 15mm to 25mm below the top surface of the battery. When placing several lead-acid batteries in a tank, the distance between adjacent lead-acid batteries and the distance between the lead-acid batteries and the inner wall of the adjacent tank should each be at least 25mm.

[0106] [Table 1]

[0107] During the test, the battery is continuously discharged at a discharge current of 20A every 25 cycles until the terminal voltage of the lead-acid battery reaches 10.2V, and the duration of discharge is recorded. Next, the battery is charged at a charge current of 5A every 15 minutes until the terminal voltage of the lead-acid battery or the specific gravity of the electrolyte (converted value at 25°C) shows a constant value with three significant digits for three consecutive cycles. This discharge and charge are also counted towards the number of times the battery lasts.

[0108] The test is terminated when it is confirmed that the capacity (Ah) calculated from the product of the discharge time and discharge current measured in the above test has fallen to 50% or less of the rated capacity of 48 Ah and does not rise again. The number of times (life times) at which the capacity reaches 50% of the rated capacity of 48 Ah is an index of life performance in heavy load cycles. The fact that the capacity does not rise again is confirmed by charging the battery to a fully charged state after the capacity has fallen to 50% of the rated capacity, and discharging it again in the same manner as above, and the capacity calculated from the product of the discharge time and discharge current at this time is 50% or less of the rated capacity. The life times can be calculated by approximating the number of cycles at 50% of the rated capacity from a graph of the number of cycles vs. capacity, which plots the discharge capacity every 25 cycles. When the amount of electrolyte reaches the lower line (LL) in the lead-acid battery case, the number of cycles at this point is determined as the lifespan due to electrolyte loss. If the battery case does not have an LL, the number of cycles when the electrolyte level drops to the top of the positive electrode strap (positive electrode shelf) is determined as the lifespan due to electrolyte loss.

[0109] The items described in this specification can be combined in any manner.

[0110] FIG. 1 shows the external appearance of an example of a lead-acid battery according to an embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0111] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with separators 4 interposed therebetween. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through-connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through-connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through-connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0112] FIG. 2 is a schematic plan view of the separator 4. The separator 4 is a laminate of a bag-shaped porous film 4a and a glass fiber mat 4b. The bag-shaped porous film 4a houses the negative electrode plate 2 of FIG. 1. The bag-shaped porous film 4a has a fold at the bottom end in FIG. 2 and an opening at the top end. At both side ends of the bag-shaped porous film 4a, a pressure-bonding portion 20 is provided linearly in the vertical direction so as to close the overlapped porous film 4a. At both side ends of the bag-shaped porous film 4a, a region 21 that is not covered by the glass fiber mat 4b is formed. The side ends of the glass fiber mat 4b are located inside the pressure-bonding portion 20. Therefore, the width w of the region 21 is 100 mm. p is the width w from the side end of the porous film 4a to the pressure-bonding portion 20 (more specifically, the outer position of the pressure-bonding portion 20). a Greater than.

[0113] The separator 4 is disposed in the lead-acid battery 1 so that the glass fiber mat 4b is in contact with the positive electrode plate 3. In the separator 4 of Fig. 2, when the back side is in contact with the positive electrode plate 3, the glass fiber mat 4b as shown on the front side is also provided on the back side.

[0114] [Example] The present invention will be specifically described below based on examples and reference examples, but the present invention is not limited to the following examples.

[0115] Lead-acid batteries E1 to E16 and R1 to R12 Each lead-acid battery was prepared according to the following procedure. (1) Preparation of the separator A resin composition containing 100 parts by weight of polyethylene, 160 parts by weight of silica particles, 80 parts by weight of paraffin oil as a pore-forming agent, and 2 parts by weight of a penetrating agent is extruded into a sheet, stretched, and then a part of the pore-forming agent is removed to prepare a microporous membrane having ribs on one side.At this time, the cooling speed of the extruded sheet and the stretching ratio are adjusted so that the ratio R of the porous film obtained by the above-mentioned procedure is the value shown in Table 2 and Table 3.

[0116] The oil content of the separator obtained by the above-mentioned procedure was 11 to 18 mass%, and the silica particle content was 60 mass%. The rib height obtained by the above-mentioned procedure was 0.2 mm. The thickness of the porous film (thickness of the base portion) obtained by the above-mentioned procedure is shown in Tables 2 and 3.

[0117] Next, the sheet-like porous film was folded in half so that the ribs were arranged on the inner surface to form a bag, and the overlapped ends were pressed together to obtain a bag-like porous film (size when laid flat: length 117 mm x width 152 mm). The pressed part was 3 mm wide, located 2 mm inside from the side end of the porous film. In Reference Examples 1 to 8 (R1 to R8), a rib was formed on the outer surface, and the bag-like porous film formed in the same manner as above was used as a separator, except that the rib height was 0.6 mm.

[0118] As shown in Fig. 2, a glass fiber mat (size under atmospheric pressure: length 117 mm × width 143 mm, average fiber diameter: 17 μm, surface density: 60 g / m) was attached to both outer surfaces of the bag-shaped porous film. 2 ) was attached with an adhesive. The width of the porous film was larger than that of the glass fiber mat, and a region with a width of 4.5 mm where the glass fiber mat was not overlapped was formed on both side edges of the porous film.

[0119] The porous film ratio R, oil content, silica particle content, base thickness, rib height, glass fiber mat size, average fiber diameter, and surface density are values ​​obtained for the porous film or glass fiber mat before the lead-acid battery was fabricated, but are almost the same as the values ​​measured by the above-mentioned procedure for the porous film or glass fiber mat removed from the lead-acid battery after fabrication.

[0120] (2) Preparation of the positive electrode plate A positive electrode paste was prepared by mixing lead oxide, reinforcing material (synthetic resin fiber), water and sulfuric acid. The positive electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy that does not contain antimony, and then aged and dried to obtain an unformed positive electrode plate with a width of 137 mm, a height of 110 mm and a thickness of 1.6 mm.

[0121] (3) Preparation of negative electrode plate A negative electrode paste was prepared by mixing lead oxide, carbon black, barium sulfate, lignin, reinforcing material (synthetic resin fiber), water and sulfuric acid. The negative electrode paste was filled into the mesh of an expanded lattice made of an antimony-free Pb-Ca-Sn alloy, and aged and dried to obtain an unformed negative electrode plate with a width of 137 mm, a height of 110 mm and a thickness of 1.3 mm. The amounts of carbon black, barium sulfate, lignin and synthetic resin fiber used were adjusted so that the contents of each component in the negative electrode plate taken out of a fully charged lead-acid battery were 0.3 mass%, 2.1 mass%, 0.1 mass% and 0.1 mass%, respectively.

[0122] (4) Preparation of lead-acid battery The unformed negative electrode plate was housed in a bag-shaped porous film of a separator. The negative electrode plate and the positive electrode plate were laminated via a separator so that the glass fiber mats attached to both outer surfaces of the bag were in contact with the positive electrode plate. In Reference Examples 1 to 8, the negative electrode plate and the positive electrode plate housed in a bag-shaped porous film were laminated. In this way, an electrode plate group was formed by seven unformed negative electrode plates and six unformed positive electrode plates.

[0123] The lugs of the positive plates and the lugs of the negative plates were welded to the positive and negative shelf parts, respectively, using the cast-on-strap method. The plate group was inserted into a polypropylene battery case, electrolyte was poured in, and chemical formation was performed inside the battery case to assemble a flooded lead-acid battery with a rated voltage of 12V and a rated capacity of 30Ah (5-hour rate capacity (capacity when discharged at a current (A) that is 1 / 5 of the Ah value indicated on the rated capacity)). Six plate groups were connected in series inside the battery case.

[0124] The electrolyte used was an aqueous sulfuric acid solution. The specific gravity of the electrolyte after formation at 20°C was 1.285.

[0125] (5) Evaluation The XRD spectrum of the porous film of the separator of the lead-acid battery E7 measured by the above-mentioned procedure is shown in Figure 3. As shown in Figure 3, the first diffraction peak corresponding to the (110) plane of the crystalline region of polyethylene was observed in the range of 2θ = 21.5 ° to 22.5 °, and the second diffraction peak corresponding to the (200) plane was observed in the range of 2θ = 23 ° to 24.5 °. A halo due to the amorphous region was observed broadly in the wide range of 2θ = 17 ° to 27 °.

[0126] The separator or the obtained lead-acid battery was used to evaluate the puncture strength of the separator, the CCA performance, and the heavy load life performance of the lead-acid battery according to the procedures described above. The heavy load life performance was evaluated according to the procedures described above for a lead-acid battery that had been fully charged once. The puncture strength was evaluated as a ratio (%) when the puncture strength of the separator used in the lead-acid battery R4 was taken as 100. The CCA performance was evaluated as a ratio (%) of the terminal voltage at 30 seconds of each lead-acid battery when the terminal voltage at 30 seconds of the lead-acid battery R4 was taken as 100.

[0127] The evaluation results are shown in Tables 2 and 3. E1 to E16 are working examples, and R1 to R12 are reference examples.

[0128] [Table 2]

[0129] As shown in Table 2, in the separator without glass fiber mat, the CCA performance is affected by the thickness of the separator, and the smaller the thickness, the higher the CCA performance (R1 to R4). However, the smaller the thickness of the separator, the lower the heavy load life performance (R1 to R4). This is thought to be because when the separator is thin, the strength of the separator decreases, making it more likely to break, and the separator will end up with a short circuit due to the fallen positive electrode material. In the case without glass fiber mat, even if the ratio R of the porous film is increased, there is no change in the CCA performance, but the strength is improved and the heavy load life performance is also improved to a certain extent (comparison between R1 to R4 and R5 to R8). For example, even if the thickness of the porous film is very thin at 100 μm, the heavy load life performance is improved by 50 cycles, from 350 cycles to 400 cycles (comparison between R1 and R5). Even if the thickness of the porous film is large, the results are not very different, and the effect of increasing the ratio R is about 25 to 50 cycles.

[0130] When the porous film is laminated with a glass fiber mat, the falling off of the positive electrode material is reduced, so the heavy load life is expected to improve to some extent. However, when the ratio R of the porous film is less than 0.6 and the thickness is 100 μm, lamination with a glass fiber mat only improves the life by 25 cycles, from 350 to 375 cycles (compare R1 and R9). Even when the thickness of the porous film is large, the results are not so different, and the improvement effect of heavy load life performance by laminating with a glass fiber mat is about 25 to 50 cycles (compare R2 to R4 and R10 to R12). On the other hand, as the thickness of the porous film increases, the resistance increases, so the CCA performance tends to decrease.

[0131] Considering the above results, even if the ratio R of the porous film is increased from 0.58 to 0.75 and laminated with a glass fiber mat, it is expected that the heavy load life performance will be improved by about 50 to 100 cycles. However, in reality, the heavy load life performance of E1 to E4 is improved by 125 to 150 cycles compared to R1 to R4, and a high value of 500 cycles or more is obtained. Moreover, the deterioration of CCA performance is also suppressed to a low level in E1 to E4. The same tendency is observed if the thickness of the porous film is 300 μm or less. From the viewpoint of obtaining excellent heavy load life performance and further improving CCA performance, the thickness of the porous film may be 250 μm or less or 200 μm or less.

[0132] [Table 3]

[0133] As shown in Table 3, when the ratio R of the porous film is 0.60 or more, by laminating it with a glass fiber mat, it is possible to ensure excellent heavy load life performance while ensuring high CCA performance (E5 to E16). Even if the thickness of the porous film is very small at 100 μm, a heavy load life performance of 450 cycles or more can be obtained.

[0134] In the examples, lead-acid batteries were produced and evaluated using porous films and plates of the above-mentioned sizes, but similar results were obtained even if the sizes of the porous films and plates were different from those described above. [Industrial Applicability]

[0135] The lead-acid battery separator according to the above aspect of the present invention is suitable for use in idling stop applications (such as lead-acid batteries for vehicles with idling stop systems) and as a starting power source for various vehicles (such as automobiles and motorcycles). The lead-acid battery separator can also be suitably used as a power source for industrial power storage devices such as electric vehicles (such as forklifts). These applications are merely examples. Applications of the lead-acid battery separator and the lead-acid battery according to the above aspect of the present invention are not limited to these. Idling stop (also called idling reduction) is sometimes referred to as IS. [Explanation of symbols]

[0136] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 4a: Porous film 4b: fiberglass mat 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug 20: Crimping section 21: Area of ​​porous film not covered by glass fiber mat

Claims

1. A separator for a lead-acid battery, the separator includes a laminate of a porous resin film and a glass fiber mat, The porous film includes a crystalline region and an amorphous region, In the X-ray diffraction spectrum of the porous film, A 1 / (A 1 +A 2 ) is 0.60 or more, A 1 is the area of ​​the first diffraction peak having the maximum peak height among the diffraction peaks corresponding to the crystalline region, A 2 is the area of ​​a second diffraction peak having the second highest peak height among the diffraction peaks corresponding to the crystalline region.

2. The lead-acid battery separator according to claim 1 , wherein the porous film has a thickness of 100 μm or more and 300 μm or less.

3. 3. The separator for a lead acid battery according to claim 1, wherein the ratio R is 0.9 or less.

4. The lead acid battery separator according to any one of claims 1 to 3, wherein the porous film contains a polyolefin.

5. The polyolefin contains at least ethylene units, the first diffraction peak corresponds to the (110) plane of the crystalline region; 5. The lead acid battery separator according to claim 4, wherein the second diffraction peak corresponds to a (200) plane of the crystalline region.

6. The separator for a lead-acid battery according to any one of claims 1 to 5, wherein the porous film has an area at least in a part of an end portion thereof that is not covered with the glass fiber mat.

7. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, The separator is a lead-acid battery separator according to any one of claims 1 to 6, the fiberglass mat being in contact with the positive plate.

Citation Information

Patent Citations

  • Battery and method for manufacturing the same

    JP2009272244A

  • Wound electrode battery, method of manufacturing the same, vehicle, apparatus, and electrode winding device

    JP2011204414A

  • Lead battery

    JP2013084362A

  • Lead acid storage battery

    JP2016139455A

  • Improved separator for reinforced flooded batteries, batteries, and related methods

    JP2019514173A